Sustainability management evolution: literature review and consolidative model - Delai, Ivete; Takahashi, Sérgio (Revista de Administração da UFSM, 2016)
Companies, as key actors in society, have been pressured to change the way they do business to integrate sustainability into their daily practices and to disclose their impacts and contributions to sustainable development. In this context, a new organizational competence – sustainability management – related to the way how companies manage and integrate sustainability issues in their core business, becomes relevant. Therefore, to understand how this competence is built or evolve over time is of major importance for their applicability. Sustainability or environmental management evolution is not new, however the extant literature points out that it is still incipient, it does not explain clearly how companies change their environmental stance over time or provide detailed definition or characteristics of each stage. In this context, this paper aims to understand the current state of sustainability management evolution models updating Kolk and Mauser (2002) work; and to present a consolidative evolution model for sustainability management derived from the complementarity of the identified models. We conclude that it is not indeed a consolidated discussion as there is not consensus regarding type of evolution, pathway followed and the very construct of sustainability.